Modernization of the “Baduy Luar” tribe in the use of the QRIS payment method: Acculturation of the “Baduy Luar” tribe - Agus Fatchurrochman; Zahrah Mahfudzah Firdaus; Bagos Budi Mulyana; Aminah Miliani; Rizqi Fitrianti (Trigin Publisher, 2023)
There is a fusion resulting from the interaction of foreign cultures with the original culture that occurs between one group and another, without leaving the original culture causing cultural acculturation. This happened in the development of Baduy culture in Lebak Regency, Banten, especially the Baduy Luar. The Baduy Tribe, which still adheres to the rules of their customs, is still exposed to modernization because the concept of culture will of course experience changes along with technological developments. This study uses the Diffusion of Innovation theory, with ethnographic methods through a qualitative approach. Data collection techniques were carried out by means of observation, interviews and literature studies. This study aims to determine the acculturation of the culture of the Baduy Luar Tribe, which incidentally still adheres to customary rules but remains flexible with technological advances, one of which is the use of digital payments in economic transactions, namely the QR Code. From this study, it can be concluded that the Baduy Tribe inevitably accepts increasingly massive technological changes, so that the ease of transactions they provide will continue to attract tourists, of course as an object of income for the livelihoods of the Baduy Luar Tribe. However, they still obey some customary rules according to their ancestors so that their local wisdom is maintained as the diversity of Indonesian culture.